Pendampingan BUMDes Melalui Program Digitalisasi untuk Meningkatkan Ekonomi Desa di Kecamatan Batanghari Kabupaten Lampung Timur - Ismunandar, Arif; Kurnia, Aang; Sidiq, Muhammad Sirojudin (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
This community service program aims to assist BUMDes through a digitization program to improve the village economy in the Batanghari sub-district of East Lampung Regency. Based on the results of problem identification, it was found that the application of digitization in the marketing of BUMDes products was not working, the marketing system was manual, and there were limitations in human resources and constraints in business unit development. Through the Participatory Action Research (PAR) approach, this program involves village officials, BUMDes administrators, and the community in a series of socialization activities, discussions, and the creation of a digital platform that emphasizes understanding and applying digital marketing in the sale of BUMDes products. The results show that BUMDes administrators have become more aware of the importance of digitalization systems and are more enthusiastic about developing BUMDes business units that have greater potential for growth and provide opportunities for experts in the management and mentoring of BUMDes business units. Thus, this program is expected to be a solution that can serve as a stepping stone for the development of similar initiatives in the future. Hopefully, this small step can contribute to creating a marketing system that will improve BUMDes business units in Batanghari Subdistrict, East Lampung Regency.